Atem / Breath: Gestalterische, ökologische und soziale Dimensionen / Morphological, Ecological and Social Dimensions (De Gruyter, 2021)
The anthology explores breath from the perspective of the arts and humanities, as well as experimental scientific and design practices. Focus is on the period from 1900 to the present day – an era during in which air has become a precarious medium, co-created and manipulated by humans. Against this backdrop, breath appears as an elusive yet vital substance that reveals connections between the physical, symbolic, technological and social realms.